Penerapan Teori Adaptasi Roy Pada Asuhan Keperawatan Pasien dengan Gagal Ginjal Kronik - Yuanita Panma (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2018)
Chronic Renal Failure (CRF) is a decrease in irreversible kidney function characterized by uremia which affects patients' biological, psychological, social and spiritual aspects. This change certainly requires good adaptation of CRF patients. Nurses can help patients adapt to changes in their level of health. The role of nurses is needed in the provision of nursing care using Roy's adaptation theory approach which is applied in the case of Mr. F, 32 years old with CRF, diabetes mellitus, diabetic retinopathy. The purpose of writing this case is to gain real experience in providing nursing care to CRF patients using Roy's adaptation theory approach. Nursing diagnoses that appear in cases of excess fluid volume are associated with decreased kidney function, fluid and sodium retention; decreased cardiac output is associated with increased cardiac workload; nutritional imbalances less than body requirements related to insufficient insulin; constipation is associated with a decrease in physical activity. The results achieved after carrying out nursing care with Roy's adaptation theory approach are edema has diminished, excess fluid volume is partially overcome; decreased cardiac output has not been resolved; blood sugar is still unstable with the help of insulin, partial deficit nutrition; partial constipation. Conclusion: Nursing care with a theory approach Roy's adaptation model is quite effective to be applied to patients with urinary system disorders, especially in cases of chronic renal failure where patients must adapt to changes that occur both biologically, psychologically, socially and culturally.